Assessing Weak-form Efficiency: A Case Study of the Saudi Stock Market (2000-2023) - Almogbel, Rashed; Almuqren, Abdulrahman (The Arab Journal of Administration, 2023)
This study aims to review the theoretical background of financial market efficiency and evaluate the level of efficiency of the financial market in the Kingdom of Saudi Arabia. Additionally, it analyzes the statistical methods that can be used to test this weak-form efficiency. This study uses secondary data, including a daily time series of closing prices from the Saudi Arabian stock market index values from 2000 to 2023. EViews 10 statistical software was used to check the stationary nature of the time series. Furthermore, these data were tested using three unit root tests: the augmented Dickey-Fuller (ADF) test, the Phillips-Perron (PP) test, and the (KPSS) test. These tests were used to evaluate the weak-form efficiency level of the Saudi Arabian financial market and verify the randomness hypothesis. The results obtained from these tests indicated that the financial market in Saudi Arabia follows the randomness hypothesis, and therefore, the market is weak-form efficient. This study emphasizes the importance of increasing transparency in financial processes and regulating the market by developing the performance of regulatory and supervisory bodies to protect investors, increasing financial awareness and education for investors, following best global practices in market management, and enhancing cooperation with international bodies to improve efficiency in the financial market.